Toddler Externalizing Behavior, Social Support, and Parenting Stress: Examining a Moderator Model. Issue 4 (19th August 2020) - Schellinger, Kriston B.; Murphy, Laura E.; Rajagopalan, Subashini; Jones, Tamekia; Hudock, Rebekah L.; Graff, J. Carolyn; Palmer, Frederick B.; Tylavsky, Frances A.
Abstract : Objective: This study examined the possible moderating role of social support on the association between child externalizing behavior and parenting stress in a cross‐sectional sample of typically developing toddlers and their mothers. Background: Child externalizing behavior problems often emerge during the toddler years and are associated with increased parenting stress. Family stress theory posits that resources (e.g., social support) may buffer the effects of stressors such as child behavior concerns. However, limited empirical research has examined the impact of social support on parenting stress in parents of typically developing toddlers. Method: The sample included 1, 036 mother–toddler dyads and was representative of the broader region in which the research took place (59% African American, 58% married/cohabitating, 53% with high school diploma). General linear models were performed. Results: The interaction term was not significant; therefore, a moderator model was not supported. However, the final model demonstrated that child behavior problems were associated with higher levels of parenting stress; and lower levels of both amount of support and satisfaction with social support were associated with additional increases in parenting stress. Conclusion: Results suggest that parents who have low levels of social support and a toddler with higher levels of externalizing behaviors are at particular risk for experiencing elevated levels of parenting stress. Implications: Given that externalizing behaviors are common during the toddler years, future research is needed to better understand how social support benefits parents of toddlers and to develop new or modify existing interventions to increase social support and reduce parenting stress.